Transformasi Cerita Arjuna Wiwaha pada Relief Candi Jago dan Lakon Ciptaning - Catur Nugroho (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2022)
This article discusses the transformation of the story Arjuna Wiwaha in the reliefs of Candi Jago and the Lakon Ciptaning. Based on the description that has been prepared, it can be concluded that three aspects, namely the history of emergence, religious aspects, and interaction aspects, can be used as simple indicators to see interactions and/or transformations in Kakawin Arjuna, reliefs of Arjuna Wiwawaha, and Lakon Ciptaning. Looking at the time intervals for the emergence and development of the three elements can give an understanding that there must be any further and deeper interactions occur. The similarities in of the religious background, namely Hinduism, become a strong reason of the communication contacts in various aspects of life, including arts. In addition, Holt said that at that time, Kakawin Arjuna, the reliefs of Arjuna Wiwawaha, and Lakon Ciptaning seemed to interact each other and it can be seen from the integration of various styles which were then stylized on the reliefs of temples in East Java that become their distinctive characteristics. Thus, the transformation that occurs in these three elements shows the changes at the level of appearance (zahir), surface, presentation, and expression, and not in the deeper areas concerning meaning, content, message, and value (value) does not experience change.